Proarrhythmic potential of metoclopramide in a sensitive whole‐heart model. Issue 6 (25th February 2021) - Wolfes, Julian; Ellermann, Christian; Burde, Sophie; Fehr, Michael; Eckardt, Lars; Frommeyer, Gerrit
Abstract: Background: Metoclopramide (MCP) is a dopamine D2 ‐receptor antagonist, mainly used to treat post‐operative or chemotherapy‐induced nausea. While it is very effective in the cure of gastric symptoms, MCP can cause severe neurologic side effects. Furthermore, there is growing evidence for severe arrhythmic side effects resulting from inhibitory effects on cardiac sodium and potassium channels. Methods and Results: Thirteen hearts of New Zealand white rabbits were retrogradely perfused, and electrophysiology studies were performed to obtain action potential duration (APD90 ) and effective refractory period (ERP). After generating baseline data, the hearts were perfused with increasing concentrations of metoclopramide (MCP 10 µM, MCP 50 µM, MCP 100 µM) and the standardized protocol was repeated for each concentration. Perfusion with MCP resulted in a significant prolongation of APD90 and QT interval. In parallel, the incidence of ventricular tachycardias was significantly increased by high doses of MCP. Conclusion: This is the first experimental study that investigated the effect of increasing doses of metoclopramide on a sensitive whole‐heart model of proarrhythmia. MCP led to a significant increase in action potential duration and QT interval; meanwhile, the number of ventricular tachycardias was significantly increased.